Body Condition Score of Bali Cows: Its Effect on Reproductive Status - Yusuf, Muhammad; Rahardja, Djoni Prawira; Toleng, Abdul Latif; Haryani, Rika; Zulkarnaim, mawardi A. Asja; Sahiruddin, Sahiruddin (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The study was aimed at scoring the body condition of Bali cows and its effect on thereproductive status. It was conducted in 14 smallholder farms in Bantaeng, South Sulawesi Province,Indonesia. A total of 64 Bali cows were involved in the study. All cows were subjected to bodycondition scoring (BCS; scale 1 - 9) and then clinically examined for reproductive status. The resultsof this study showed that most of cows had lower BCS (68%) and only 32% had BCS 5 or greater. Aproportion of cows with parities 1 and 2 were 61%, higher than parities 3 and 4; 28% and parity 5 orgreater; 25%. This study also noted that proportions of cows pregnant, cyclic and anestrous were25%, 9%, and 66%, respectively. Interval from calving (mean ± SD) to conception of these Bali cowswas relatively longer 191.3 ± 115.7 days and it expected calving interval of the cows approximately476 days. In conclusion, the Bali cows exhibited lower reproductive performance and lower BCS was the contributory factor. Key Words: Bali Cows, BCS, Reproductive Status, Reproductive Performance